VB.Net Web Developer's Guide. - Wakefield, Cameron (Syngress Pub., 2001)
Visual Basic has long been the language of choice when designing Windows-based applications and the Web. Touted as both the most popular and productive computing language, Visual Basic has amassed quite a following of devoted programmers, and is a sought after programming skill. With the introduction of .NET Enterprise, Microsoft launch VB.NET, offering a streamlined, simplified version of Visual Basic language. With increased power, scalability, functionality and reliability, VB.NET is positioned to be the most productive tool in a programmer's toolbox. VB.NET Developer's Guide is written for.